Fabrication of Porous Thin Film Core for Micro-Fluxgate by Using Anodic Aluminum Oxide Templates - Lv, Hui; Liu, Shibin (Asian Journal of Chemistry, 2013)
Porous thin film core is conducive to impelling the micro-fluxgate toward the direction of low power consumption and high sensitivity. In this experiment, anodic aluminum oxide templates were obtained by two-step anodization process. We could obtain a copper template by two-step replication of the anodic aluminum oxide template. Furthermore, porous Fe-Ni thin film was fabricated by magnetron sputtering on the copper template. The morphology of the porous film complies with the anticipation. The characteristic of the pores can be changed by adjusting the experimental parameters.